IMPLEMENTASI NILAI-NILAI SPIRITUAL UNTUK MENINGKATKAN AKHLAK SISWA DI SMPN 2 KOTA BIMA - Ilham, Ilham; Aprianingsih, Isratul (Kreatif: Jurnal Pemikiran Pendidikan Agama Islam, 2024)
Determine the implementation of spiritual values in this study aims to improve the morals of students at SMPN 2 Bima City. In this study using decriptive qualitative methods. While the subjects in this study were PAI teachers and students. Interview, observation, and documentation. Data analysis techniques, namely by collecting data, reducing data, presenting data, and drawing conclusions. Checking the validity of the findings, namely source triagulation and data triagulation. The results of the study state that: 1) Implementation of Spiritual Values to Improve morals Student get used to doing culture 3S, sebumi, memorizing short surahs, imtaq, and collecting infaq. Through their activities at school, students can demonstrate commendable character in the school environment, such as speaking kind and humble words to teachers and friends, and activities in accordance with beliefs in daily activities. 2) Obstacles in implementing spiritual values to improve student morals, are student awareness, limited time for implementation, inadequate worship facilities, student environment or association, and parents or family.